Ministry of Finance Decree No. 460 of the Year 2023 On Accrediting the Percentage of Change in Calculation of Foreign Currency Procurement Differences Upon Determining the Income Tax Base for the Year 2022 = وزارة المالية قرار رقم 460 لسنة 2023 بشأن اعتماد نسبة التغيير فى حساب فروق تدبير العملة الأجنبية عند تحديد وعاء الضريبة على الدخل عن عام 2022 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic